The influence of financial literacy and the lifestyle housewives on family financial management - Rifngah, Dewi Idadir Rifngah; Suryadinata, Ningrum (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2024)
Good financial literacy can help families achieve financial stability and improve mutual well-being. Lifestyle greatly affects family finances and how housewives can balance between the needs to still be able to manage finances well. Have stable finances so that you are wise in determining future savings and long-term investments. The Influence of Financial Literacy and Housewives' Lifestyle on Family Financial Management. This study aims to determine the influence of financial literacy and lifestyle of housewives on family financial management in Sumberejo village. The data collection method used in this study was questionnaire and data analysis using multiple linear regression. The result of the showed that financial literacy on financial management and lifestyle on financial management. It can be partially concluded that “there is an influence of financial literacy and lifestyle on family financial management”